Experimental investigation of the impact of irradiation damages on the mechanical properties of tungsten - Robert Lürbke; J. Riesch; A. Feichtmayer; B. Curzadd; T. Höschen; R. Neu (Nuclear Materials and Energy, 2025)
Tungsten (W) is considered the preferred plasma-facing material (PFM) in future magnetic confinement fusion reactors. There it will be exposed to high heat fluxes and intense neutron radiation. Neutron irradiation could have an embrittling effect on is expected to cause irradiation hardening and embrittling of the material, which poses a significant threat for the structural integrity of tungsten components. High-energy self-ion irradiation can be used to simulate the displacement damage caused by neutrons irradiation in tungsten. Due to the low penetration depth of heavy ion radiation in W, thin W wires are used as a model system since they can be irradiated throughout their full entire volume. The very fine microstructure of such wires allows size effects to be reduced. To measure the effect of heavy self-ion irradiation, 16 μm diameter W wires were thinned to 5 μm and then irradiated with 20.3 MeV W6+ ions. Mechanical properties were determined by tensile testing and scanning electron microscopy (SEM) imaging of the area reduction as a measurement for ductility. Ten wires each were irradiated at 0.2 dpa, 1 dpa, and 10 dpa and compared with the as-received material. In the as-fabricated state, these wires show a pronounced ductile behavior. The irradiation damage did not alter the mechanical properties or the area reduction of the samples.